Confusing new approach to public services - Nayar, K.R. (2004)
The modernising government programme (MGP) funded by ADB is geared towards a market-driven policy aimed at the gradual downsizing of public sector health services. The MGP strategy and some of its covert objectives will gradually extend the scope of privatisation of healthcare, creating chasms within the population and demolish welfare traditions. - Reproduced.
Keywords: Health services